Penerapan Literasi Digital dan Pemasaran Produk Berbasis Teknologi di Desa Banjarwaru - Vikasari, Cahya; Prabowo, Annas Setiawan; Widianingsih, Betti; Bahroni, Isa; Romadloni, Annisa (Politeknik Negeri Cilacap, 2025)
Banjarwaru Village faces marketing challenges for bamboo weaving products due to the limited local market and lack of coordination. The proposed solution is the establishment of a village coordination unit for business and marketing integration, as well as digital literacy training for artisans. The methods include market needs analysis, selection of application managers, coordination of product photography, and intensive training on digital marketing and e-commerce. As a result, artisans can optimize digital technology, expand market reach, and enhance product competitiveness. This program is capable of increasing artisans' knowledge and skills, as well as supporting the economic growth of Banjarwaru Village through online marketing and e-commerce